IMPLEMENTASI SISTEM MANAJEMEN INVENTARIS BERBASIS TEKNOLOGI INFORMASI UNTUK OPTIMALISASI RANTAI PASOK DI INDUSTRI RITEL - Noviani, Lona; Qurohman, Tauffik (Universitas Banten Jaya, 2024)
This study aims to develop and implement an IT-based inventory management system in the retail industry to optimize the supply chain. By utilizing IT, this system is expected to improve stock management efficiency, reduce operational costs, and increase customer satisfaction. The research methodology involves needs analysis, system design, testing, and implementation of an inventory management system in several retail branches. The implementation results show significant improvements in inventory data accuracy, speed of response to market demand, and reduction in storage costs. A case study of one of the retail branches implementing this system shows a 15% decrease in inventory costs and a 20% increase in customer satisfaction in the first six months after implementation. This study concludes that an IT-based inventory management system is effective in optimizing the supply chain in the retail industry and providing added value to customers.